Maternal excess adiposity and serum 25-hydroxyvitamin D < 50 nmol/L are associated with elevated whole body fat mass in healthy breastfed neonates - Maryam Razaghi; Nathalie Gharibeh; Catherine A. Vanstone; Olusola F. Sotunde; Shu Qin Wei; Dayre McNally; Frank Rauch; Glenville Jones; Hope A. Weiler (BMC, 2022)
Abstract Background Vitamin D status of pregnant women is associated with body composition of the offspring. The objective of this study was to assess whether the association between maternal vitamin D status and neonatal adiposity is modified by maternal adiposity preconception. Methods Healthy mothers and their term appropriate weight for gestational age (AGA) infants (n = 142; 59% male, Greater Montreal, March 2016-2019) were studied at birth and 1 month postpartum (2-6 weeks). Newborn (24-36 h) serum was collected to measure total 25-hydroxyvitamin D [25(OH)D] (immunoassay); maternal pre-pregnancy BMI was obtained from the medical record. Anthropometry, body composition (dual-energy X-ray absorptiometry) and serum 25(OH)D were measured at 2-6 weeks postpartum in mothers and infants. Mothers were grouped into 4 categories based on their vitamin D status (sufficient 25(OH)D ≥ 50 nmol/L vs. at risk of being insufficient < 50 nmol/L) and pre-pregnancy BMI (< 25 vs. ≥25 kg/m2): insufficient-recommended weight (I-RW, n = 24); insufficient-overweight/obese (I-OW/O, n = 21); sufficient-recommended weight (S-RW, n = 69); and sufficient-overweight/obese (S-OW/O, n = 28). Partial correlation and linear fixed effects model were used while adjusting for covariates. Results At birth, infant serum 25(OH)D mean concentrations were below 50 nmol/L, the cut-point for sufficiency, for both maternal pre-pregnancy BMI categories; 47.8 [95%CI: 43.8, 51.9] nmol/L if BMI < 25 kg/m2 and 38.1 [95%CI: 33.5, 42.7] nmol/L if BMI ≥25 kg/m2. Infant serum 25(OH)D concentrations at birth (r = 0.77; P < 0.0001) and 1 month (r = 0.59, P < 0.0001) were positively correlated with maternal postpartum serum 25(OH)D concentrations. Maternal serum 25(OH)D concentration was weakly correlated with maternal percent whole body fat mass (r = − 0.26, P = 0.002). Infants of mothers in I-OW/O had higher fat mass versus those of mothers in S-OW/O (914.0 [95%CI: 766.4, 1061.6] vs. 780.7 [95%CI: 659.3, 902.0] g; effect size [Hedges' g: 0.42]; P = 0.04 adjusting for covariates) with magnitude of difference of 220.4 g or ~ 28% difference. Conclusions Maternal and neonatal vitamin D status are positively correlated. In this study, maternal adiposity and serum 25(OH)D < 50 nmol/L are dual exposures for neonatal adiposity. These findings reinforce the importance of vitamin D supplementation early in infancy irrespective of vitamin D stores acquired in utero and maternal weight status.